Trends and outcomes in the management of vascular trauma: institutional experience at a level 1 trauma center - Weller, Justin; Bowles, Madison (International Surgery Journal, 2021)
Background: Vascular trauma remains a complex area for clinicians and its management is constantly evolving. The increasing use of endovascular modalities and non-operative management has led to significant changes in the treatment of vascular trauma. The aim of this study was to identify the current management and outcomes of vascular trauma at a Level 1 trauma centre in Queensland, Australia and compare this with the current literature. Methods: All individuals who presented to GCUH with vascular injuries between January 2014 and December 2019 were identified from the GCUH trauma database. A descriptive analysis was performed on this cohort. Results: 213 patients were identified in our cohort; 51 were managed non-operatively, 121 were managed with open surgery, 37 were managed endovascularly and 4 had a combination of open and endovascular intervention. Conclusions: The proportion of vascular injuries managed with endovascular interventions or non-operatively has increased within the study period. This study shows that the trends of management for vascular trauma in Australia are consistent with recent international literature.